2022
DOI: 10.1186/s13071-022-05243-5
|View full text |Cite
|
Sign up to set email alerts
|

Dipylidium caninum in the twenty-first century: epidemiological studies and reported cases in companion animals and humans

Abstract: Background Dipilidiosis is a parasitic disease caused by the tapeworm Dipylidium caninum. Fleas and, less frequently, lice act as an intermediate host, and their ingestion is required for infection to occur. While the disease mainly affects domestic and wild carnivores, it is also considered a zoonotic disease, with most human cases reported in children. Dipylidium caninum is considered to be the most common tapeworm infesting companion animals, but dipilidosis in humans is rare. The aims of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 115 publications
1
24
1
Order By: Relevance
“…Dipylidium caninum was the only cestode found (0.85%, 3/353: in isolated and mixed infections), in agreement with studies that reported it to be the cestode species most observed in dogs (Khan et al, 2020;Rousseau et al, 2022). Different occurrences of D. caninum were found in other locations, such as 0.1% (3/3099) in domiciled dogs from São Paulo, São Paulo, Brazil (Ferreira et al, 2016); 13.7% (11/80) in stray dogs from Manaus, Amazonas, Brazil (Pereira & Barbosa, 2013); and 11.8% (18/152) in domiciled and stray dogs from Lower Dir district, Pakistan (Khan et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Dipylidium caninum was the only cestode found (0.85%, 3/353: in isolated and mixed infections), in agreement with studies that reported it to be the cestode species most observed in dogs (Khan et al, 2020;Rousseau et al, 2022). Different occurrences of D. caninum were found in other locations, such as 0.1% (3/3099) in domiciled dogs from São Paulo, São Paulo, Brazil (Ferreira et al, 2016); 13.7% (11/80) in stray dogs from Manaus, Amazonas, Brazil (Pereira & Barbosa, 2013); and 11.8% (18/152) in domiciled and stray dogs from Lower Dir district, Pakistan (Khan et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…This number is as small as the research conducted Bashofi et al (2015) on wild cats in Bogor and found no D. caninum eggs at all from 30 samples examined. Infections caused by D. caninum in humans need to be considered because they are asymptomatic or non-specific symptoms such as abdominal pain, bloating, diarrhea, difficulty defecating, loss of appetite, pruritus of the anus, sleep disorders, and Prevalence of Gastrointestinal Parasitic in Dogs and Cats at Kaki 4 and K-5 Clinics in Kediri City hyperactivity (Rousseau et al, 2022). Anthelmintics that can be used to treat D. caninum infection are the praziquntel or epsiprantel groups (Chelladurai et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, the parasite displayed low prevalence in children in Egypt [ 35 ]. Likewise, a few human cases, mostly in children, have been reported worldwide [ 36 ].…”
Section: Cestodesmentioning
confidence: 99%